If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7y + 4 + -1y + 8 = 0 Reorder the terms: 4 + 8 + 7y + -1y = 0 Combine like terms: 4 + 8 = 12 12 + 7y + -1y = 0 Combine like terms: 7y + -1y = 6y 12 + 6y = 0 Solving 12 + 6y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 6y = 0 + -12 Combine like terms: 12 + -12 = 0 0 + 6y = 0 + -12 6y = 0 + -12 Combine like terms: 0 + -12 = -12 6y = -12 Divide each side by '6'. y = -2 Simplifying y = -2
| 4m-1/2=5+m | | 5(v+5)=-3(3v-7)+2v | | 3x+1=11x-4 | | 2x+(2*3x+5)=945 | | 7(2n+4)=9(4n+5)+7 | | 4d^2-2d=0 | | 4/5x=32 | | -3x+4=4x-17 | | 6(x-2)/9=4(x+1)/12 | | 7(x+1)+7=2x+5(3+x) | | -9+12x+13k-5x-2k-25= | | 5x-3=-3x+1 | | -19=5t | | -9(x-10)=17-8x | | 3x+(2*3x+5)=945 | | 6x-(7x+6)=4x-26 | | y=3.2x+0.7 | | 1.50x+2.00=20 | | 14=-7u | | 6y+2(y-9)=6(y+1)-3 | | x-5x-60-x-13=-17 | | 7(2n+5)=8(6n+1)+6 | | k(2k+2)-6(2k+4)=k(2k-4)+(6k+9) | | -30/6= | | x+12=2x+3+9(x-3) | | 3(x-4)-8=-5(-5x+2)-8x | | 15x+21=4(3x+6)+3x-3 | | 9+36/3^2 | | 5(x-3)=2(x+9) | | 3x-5=12x-18 | | 5(y+8)+y=3(y+4)-8 | | 8x+2=8(x-1) |